Book ‘Public Transit Planning and Operation: Modeling, Practice and Behavior’ review - Liu, Tao (Transport, 2015)
"Book ‘Public Transit Planning and Operation: Modeling, Practice and Behavior’ review." Transport, 30(4), pp. 448–450